The customs union issue - Viner, Jacob, 1892-1970 (Oxford University Press, 2014)
Jacob Viner's The Customs Union Issue was originally published in 1950 by the Carnegie Endowment for International Peace. It set the framework for the contemporary debate over the benefits or otherwise of preferential trading agreements such as the European Union, NAFTA, and APEC. Viner developed the concepts of trade creation and diversion in this work as he pioneered the analysis of the global politics of trade agreements. This revival of Viner's classic work includes an introduction that places this book in the context of his own intellectual development and the economic and political situa.